Functional Dissection of SseF, a Membrane-Integral Effector Protein of Intracellular Salmonella enterica - Müller, Petra; Chikkaballi, Deepak; Hensel, Michael (PLOS ONE, 2012)
During intracellular life, the bacterial pathogen Salmonella enterica translocates a complex cocktail of effector proteins by means of the SPI2-encoded type III secretions system. The effectors jointly modify the endosomal system and vesicular transport in host cells. SseF and SseG are two effectors encoded by genes within Salmonella Pathogenicity Island 2 and both effector associate with endosomal membranes and microtubules and are involved in the formation of Salmonella-induced filaments. Our previous deletional analyses identified protein domains of SseF required for the effector function. Here we present a detailed mutational analysis that identifies a short hydrophobic motif as functionally essential. We demonstrate that SseF and SseG are still functional if translocated as a single fusion protein, but also mediate effector function if translocated in cells co-infected with sseF and sseG strains. SseF has characteristics of an integral membrane protein after translocation into host cells.